Labour standards, export performance and labour mobility in Asean - Ng, Kar Yee (2016)
Labour standards are norms and rules that govern the working conditions and industrial relations, which include the right of workers to organize collectively and represented by organization, the right to take industrial actions, wages and hours of works, workplace health and safety regulations and compensations to injured workers, and etc. Issues pertaining to labour standards are on-going debates among the researchers and policy makers, especially the concerns about the increased exports in developing countries at the expense of workers’ welfare. In the context of the Association of South East Asia Nations (ASEAN) countries, most of these countries experienced export-led growth in the recent decades. In the meantime, the labour standards in these countries do not show much improvement, if not worsen. For instance, trade union density rates are declining over the years, longer average weekly hours worked (> 40hours), and relatively more occupational accidents than other regions.Using cross-sectional time series data sets, this study concentrates on how labour standards are related to the core elements described in ASEAN Economic Community Blueprint. Specifically, this study examines the effects of labour standards on export performance. Next, the study further analyses the impact of foreign labour standards on ASEAN’s labour standards. Lastly, this study investigates the role of labour standards in explaining the labour mobility pattern in ASEAN countries. This study uses numbers of strikes and lockouts, average weekly working hours, trade union density rates and casesFirstly, this study applies Cheng and Wall (2005) 2-step fixed effect model to examine the effect of labour standards on exports. The empirical evidence suggests that ASEAN countries with lower labour standards do not outperform their competitors in exports.The effects of labour standards on export performance vary depending on the indicators used to measure the level of labour standards. Estimates for average actual weekly hours worked imply that cost effects outweigh productivity effects. In contrast, estimates for numbers of strikes support the argument that higher labour standards would increase labour productivity, which in turn improves exports. However, the study finds insufficient evidence to conclude the effect of total cases of injuries on export performance.of workplace injuries to proxy the labour standards.Firstly, this study applies Cheng and Wall (2005) 2-step fixed effect model to examine the effect of labour standards on exports. The empirical evidence suggests that ASEAN countries with lower labour standards do not outperform their competitors in exports. The effects of labour standards on export performance vary depending on the indicators used to measure the level of labour standards. Estimates for average actual weekly hours worked imply that cost effects outweigh productivity effects. In contrast, estimates for numbers of strikes support the argument that higher labour standards would increase labour productivity, which in turn improves exports. However, the study finds insufficient evidence to conclude the effect of total cases of injuries on export performance.Secondly, this study employs panel ordinary least squares (pooled OLS), random and fixed effect models to assess the impact of foreign labour standards on domestic labour standards. The study obtains mixed results pertaining to the impact of foreign labour standards on domestic labour standards. When the level of labour standards is represented by the numbers of strikes and lockouts that have been carried out in the countries, the estimated coefficient indicates that strike activities in foreign countries have an insignificant effect on the level of labour standards in ASEAN countries. Meanwhile, the estimation results support the ‘race to the bottom’ hypothesis on labour standards among the countries when the other indicators, which are total cases of injuries and trade union density rates, are used to proxy the level of labour standards. Lastly, this study utilizes pooled OLS estimation technique in the attempt to investigate the role of labour standards on labour mobility. The empirical study also obtains mixed results to explain the effect of labour standards on bilateral migration flows in ASEAN countries. When the level of labour standards is represented by numbers of strikes and/ or average weekly hours worked, the results demonstrate that better labour standards increase the bilateral migration flows among countries selected in the analysis. Nonetheless, the migration increases when there are more cases of occupational injuries reported, which implies that better working conditions do not attract workers to move. Based on the obtained results, this study concludes that there is a need to re-examine the investment and trade regulations and labour policies of the ASEAN countries, especially those countries that rely heavily on multinational enterprises and foreign labour. These policies should focus on how to increase exports without undermining the welfare of labour. Although ASEAN countries had worked hard to increase the labour standards and provide strong legal protection for collective labour rights, the evidence signals that repeated violations of such rights continue to happen in practice. Thus, policymakers also face challenges in implementing labour standards and ensuring that the parties involved comply with the established rules and regulations.